Terms of endearment [videorecording (Blu-Ray)] - Brooks, James L.; Nicholson, Jack; MacLaine, Shirley, 1934-; Daniels, Jeff, 1955-; DeVito, Danny (Paramount, 2017)
Follows the rocky and passionate relationship between a mother and daughter from birth to death.